Pengaruh Content Marketing dan Harga Flash Sale Terhadap Keputusan Pembelian Tiktok Shop: Studi Kasus Mahasiswa Manajemen Perguruan Tinggi Swasta di Cikarang - Sarmin Sarmin; Soedjatmoko Soedjatmoko; Muhammad Arif Febrianto; Muhamad Daman Ardian (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This research is titled "The Influence of Content marketingand Flash sale Prices on Purchase Decisions at TikTok Shop on Management Students in Cikarang". The background of this research is the rise of TikTokShop, which uses content marketingtactics and flash sale pricing. However, there is still little research done on how these tactics affect consumer choices, especially among college students who should be aware of these marketing tactics. The purpose of this study is to analyze the partial and simultaneous influence of these two factors. Using purposive sampling techniques, 380 Management students who used TikTokShop were given an online questionnaire as part of a quantitative research approach. The study's findings show that the price of flash sales and content marketingsignificantly influences consumer purchasing decisions, either partially or simultaneously. These two variables influenced 25.4% of purchase decisions, while other factors influenced 74.6%, with an R2 value of 0.254. With a t-value of 6.286, content marketingemerged as the most significant variable, suggesting that content marketingis more successful than flash sales in attracting purchase interest. Businesses looking to optimize their TikTokShop content marketingstrategy can use these findings as a guide.